Imported fascioliasis in non-endemic countries: a case series and review of the literature - Paola Rodari; Maria Luca D'Errico; Andrea Angheben; Leonardo Motta; Veronica Andrea Fittipaldo; Dora Buonfrate; Federico Giovanni Gobbi (Travel Medicine and Infectious Disease)
Background: Fascioliasis is one of the most neglected foodborne zoonotic infectious disease, caused by the trematodes Fasciola hepatica and Fasciola gigantica. In last decades, it emerged as a public health problem worldwide, due to the substantial number of human infections. Fascioliasis has also been described in travellers and migrants, with relevance in Travel Medicine. Methods: We reported four cases of imported human fascioliasis diagnosed in our Department between 2011 and 2023. Literature search was performed on MEDLINE and Embase. We included case reports and case series on patients diagnosed with imported fascioliasis in non-endemic countries to summarize diagnostic and therapeutic approaches. Results: We retrieved 46 cases of imported fascioliasis, mostly acquired after stay in countries of South East Asia (41.3 %) and Africa (34.8 %). Forty patients (86.9 %) presented with symptoms, particularly low-grade fever and abdominal pain. Eosinophilia was found in 94.4 %. When performed, serology was positive in almost all patients (36/37, 97.3 %), while parasitological stool examination was positive only in a few cases (5/32, 15.6 %). In 12 cases, adult worm was removed by endoscopic technique, while in six cases fascioliasis was diagnosed after liver biopsy or resection. Triclabendazole was administered 33 cases, with excellent outcome. Discussion: Diagnosis of fascioliasis is complex in non-endemic settings, and a high index of suspicion is crucial. The presence of eosinophilia, fever and hepatic lesions in travellers or migrants should rise suspicion, and serological tests may confirm the diagnosis. Triclabendazole remains the drug of choice, despite unavailability in many countries.